Diversitas Arthropoda Tanah Di Area Restorasi Ranu Pani Kabupaten Lumajang - ardillah, Jr sulthan; Leksono, Amin Setyo; Hakim, Luchman (Biotropika: Journal of Tropical Biology, 2014)
Ranu Pani is damaged areas ecosystem, so restoration activities are integrated to aspects of the ecosystem biotic and abiotic components are required. The important factor to succeed the restoration is land health. Arthropods has a very important role for the ecosystem, either directly or indirectly. The role of arthropods on ecosystems such as pollinators, decomposers, predators, parasitoids and bio-indicators. The aim of this study were to determine the type of soil arthropods found in Ranu Pani land restoration and to determine their roles in Ranu Pani and to determine the diversity index of soil arthropods in Ranu Pani. The method used in this research was Falltrap Pit (Bottle trap). Arthropods put in a bottle that has been filled with a solution of 70 % alcohol. Arthropods were identified in the laboratory. Arthropods from Ranu Pani restoration land was 916 specimens, consisting of 13 family. Three orders of arthropods with the largest number were Orthoptera (49.59 %), Amphipoda (44.17 %), Opiliones (6.23 %). Important value index (INP) of family land arthropods in the first year were Talitridae (72.658 %), Gryllidae (31.995 %), Acrididae (53.379 %) and larvae of Noctuidae (16.092 %). The dominant family in the second year were Talitridae (48.935 %), Gryllidae (73.057 %), Carabidae (23.769%) and Oxyopidae (14.147 %). The air temperature and the lower the light intensity could increased the abundance of soil arthropods. The Shannon-Wiener index of the second year location was lower (H = 1.899) compared to the first year location (H = 2.523). Key words: Arthropods, ecological indicators, community structure, restoration area.